PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP EARNINGS MANAGEMENT : A POLITICAL COST PERSPECTIVE - Rani Evadewi; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
This study aims to obtain evidence about the influence of corporate social responsibility disclosure (CSR Disclosure) to earnings management . Control variables used include firm size as a proxy of the political cost, leverage , return on assets (ROA), and sales growth . Measurement of Earnings Management based on the calculation of discretionary Accruals . While the measurement of corporate social responsibility CSR index based on guidelines issued by the Global Reporting Initiative (GRI), which is seen from company’s annual report (annual report) and/ or sustainability reports (sustainability report).The population used in this study are manufacturing and mining companies listed on the Indonesia Stock Exchange in 2010-2012. This study uses purposive sampling method for data selection. The total sample used in this study were 170 companies. Data analysis was performed with the classical assumption and hypothesis testing of regression method. The results of this study indicate that the presence of a significant positive relationship between earnings management with CSR Disclosure without political cost for companies in the manufacturing industry. As for companies in the mining industry, found a significant negative relationship between earnings management with CSR Disclosure when the political cost is taken into account. The study also proved that ROA has significant positif effect on earnings management practices at companies in the manufacturing industry in Indonesia. Then, in the mining industry, control variables which are firm size, leverage and ROA have significant positive effect on Earnings Management.